A Blue or a Green Beret? Some Thoughts on the Author’s Role in Translating Modern Norwegian Literature - Drozdowska, Karolina (Porównania, 2020)
The aim of this paper is to present the role of the original text’s author as an actor in the process of translating modern Norwegian literature into Polish. Basing on the actor-network theory (ANT) and experience from my own work as a literary translator, I present the features of different types of interaction between the author and the translator, placing those interactions in the context of the specific conditions of the Norwegian book market that, because of its high level of integration, stimulates and encourages such interactions. I reflect upon the role of the author in the translation process presenting three categories – so-called “levels” of author-translator collaboration, conducting case studies of the translation processes I myself have been involved in.